VIDEO CONFERENCES IN TEACHING EFL: A CASE STUDY OF USING ZOOM - Hastomo, Tommy; Marcela, Eny Dwi; Sutiyono, Akhmad (Lentera: Jurnal Ilmiah Kependidikan, 2021)
This study discovers a case study using a Zoom video conference to teach English to English Department Students (N=70) in STKIP-PGRI Bandar Lampung, Indonesia. This study aimed to uncover students’ perception of video conference activities' enlightening benefit and determine if Zoom improves writing ability. During the first semester, the instructors conducted 16 meetings in the Zoom conference, including materials and exercises to explore the writing subject. This research exposes the effectiveness of Zoom as an educational platform for teaching English. The researcher utilized open-response questionnaires as a qualitative and quantitative research method consisting of pre-test and post-test to evaluate the students’ writing ability.